Gamified System for Entrepreneurship among Peruvian University Students (Docentes 2.0 Journal, 2026)
Experiential learning and gamification have emerged as innovative strategies to strengthen entrepreneurship education in university settings by promoting active participation and developing complex competencies. In this regard, the objective of this research was to design and validate a gamified System dubbed Pukllay 2.0 to foster entrepreneurial competencies among university students. he study was framed within the pragmatic paradigm, employing a hypothetico-deductive method and a concurrent mixed-methods design featuring triangulation. It utilized a quasi-experimental design involving pretest-posttest measurements with non-equivalent groups, characterized as applied-explanatory and short-range research. The study population comprised 42 university students, divided into an experimental and a control group. Validated instruments were used to measure usability, user experience, engagement, and entrepreneurial competencies, supplemented by semi-structured interviews. The results demonstrated high levels of usability and a positive user experience, as well as statistically significant improvements in opportunity recognition, creativity, and presentation skills; meanwhile, other competencies showed positive trends that did not reach statistical significance. In conclusion, the gamified system proved to be an effective strategy for strengthening entrepreneurial competencies, boosting motivation, and promoting active participation, thereby fostering a meaningful learning environment grounded in experimentation.
Keywords: Entrepreneurship; gamification; university; scale; validation